Systemically Important Banks – Risk Transfer in the Euro Area - Koleśnik, Jan (Journal of Finance and Financial Law, 2023)
The purpose of the article/hypothesis. The main aim of this article is to assess the direction and scale of risk transfer via systemically important banks in the euro area. This paper also critically analyses and proposes practical applications of supervisory and complex measures of SIBs identification. Methodology. The impact of systemic risk transfer via O-SIBs on the home and host countries was examined using the supervisory measure of an individual bank’s contribution in the national systemic risk. Additionally, the SRISK model was used. Results of the research. The conducted research has shown that the nature of risk transfer is potentially unidirectional, i.e., from the ‘old EU’ countries to the other countries in the same group or to the ‘new EU’ states. Also, three other SIBs have been found to pose a greater threat to the national banking system than their parent entities do in their home countries. Moreover, it has been demonstrated that in three countries, the aggregate risk contribution of the local O-SIBs – being subsidiaries of O-SIBs from other Eurozone countries – exceeds 25%.